Options for REDD+ voluntary certification to ensure net GHG benefits, poverty alleviation, sustainable management of forests and biodiversity conservation - Merger, E.; Dutschke, M.; Verchot, Louis V. (2011)
Our objective was to compare and evaluate the practical applicability to REDD+ of ten forest management, social, environmental and carbon standards that are currently active worldwide: Climate, Community and Biodiversity (CCB), CCB REDD+ Social and Environmental Standards (CCBA REDD+ S&E), CarbonFix Standard (CFS), Forest Stewardship Council (FSC), Global Conservation Standard (GCS), ISO 14064:2006, Plan Vivo Standard, Programme for Endorsement of Forest Certification (PEFC), SOCIALCARBON Standard and the Voluntary Carbon Standard (VCS). We developed a framework for evaluation of these standards relative to each other using four substantive criteria: (1) poverty alleviation, (2) sustainable management of forests (SMF), (3) biodiversity protection, (4) quantification and assessment of net greenhouse gas (GHG) benefits; and two procedural criteria: (5) monitoring and reporting, and (6) certification procedures. REDD programs require assessment of GHG benefits, monitoring, reporting and certification. Our analysis shows that only the Voluntary Carbon Standard (VCS) treats these three criteria comprehensively. No standard provides comprehensive coverage of the social and other environmental criteria. FSC, PEFC and CarbonFix provide comprehensive assessments of the sustainable forest management criterion. CCBA REDD+ S&E, CCB, and GCS provide comprehensive coverage of the biodiversity and poverty alleviation criteria. Experience in using these standards in pilot projects shows that projects are currently combining several standards as part of their strategy to improve their ability to attract investment, but costs of implementing several certification schemes is a concern. We conclude that voluntary certification provides useful practical experience that should feed into the design of the international REDD+ regime